2021
DOI: 10.3390/v13122439
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Kit for Rapid Immunochromatographic Detection of Sacbrood Virus Infecting Apis cerana (AcSBV) Based on Polyclonal and Monoclonal Antibodies Raised against Recombinant VP1 and VP2 Expressed in Escherichia coli

Abstract: A Korean isolate of the sacbrood virus infecting Apis cerana (AcSBV-Kor) is the most destructive honeybee virus, causing serious economic damage losses in Korean apiculture. To address this, here, we attempted to develop an assay for the rapid detection of AcSBV-Kor based on immunochromatographic detection of constituent viral proteins. Genes encoding VP1 and VP2 proteins of AcSBV-Kor were cloned into an expression vector (pET-28a) and expressed in Escherichia coli BL21(DE3). During purification, recombinant V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…In our study, the sensitivity threshold of the lateral flow assay was determined to be 0.625 µg/mL for the Δ60VP1 antigen. This sensitivity is lower than the immunochromatography strip developed by Lee et al (2021) . They utilized paired polyclonal antibodies and MAB specific to VP1 and VP2 of the Sacbrood virus, an insect virus.…”
Section: Discussionmentioning
confidence: 83%
“…In our study, the sensitivity threshold of the lateral flow assay was determined to be 0.625 µg/mL for the Δ60VP1 antigen. This sensitivity is lower than the immunochromatography strip developed by Lee et al (2021) . They utilized paired polyclonal antibodies and MAB specific to VP1 and VP2 of the Sacbrood virus, an insect virus.…”
Section: Discussionmentioning
confidence: 83%
“…The colloidal gold-labeled antibody-based immunochromatographic strip is rapid, easy to operate, low cost, is not dependent on professional equipment, and is widely used in poultry disease detection ( Li et al, 2013 ; Qian et al, 2015 ; Yu et al, 2018 ; Wang et al, 2019 ; Yu et al, 2020 ), as well as in certain other fields ( Zhao et al, 2008 ; Li et al, 2012 ; Meng et al, 2014 ; Li et al, 2020 ; Lee et al, 2021 ; Li et al, 2021 ; Guo et al, 2023 ). Zhang et al, (2010) reported the use of IBV colloidal gold immunochromatography for the first time, but their method was only used to detect the antibodies against IBV.…”
Section: Introductionmentioning
confidence: 99%